Presentation of the dossier. The permanent revolution: Trotsky and the Anti-Imperialist Struggle in the 21st Century - Silva, Michel (Pacha. Revista de Estudios Contemporáneos del Sur Global, 2020)
Apresentação do dossiê. A revolução permanente: Trotsky e a luta anti-imperialista no século XXI